2009
DOI: 10.1177/039463200902200427
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and E-Nitric Oxide Synthase-Mediated Regenerative Response Occurring upon Autologous and Heterologous Bone Grafts

Abstract: Bone regeneration procedures allow oral rehabilitation with dental implants also in edentulous ridges with severe bone atrophy. The integration of grafted materials with the host tissue can initiate regenerative, inflammatory and apoptotic response. Since molecular mechanisms exist at the basis of such response, the aim of this work is to investigate, by immunohistochemical analyses, the expression of proteins involved in the graft integration process, in parallel to clinical and histological modifications, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
10
0
2
Order By: Relevance
“…Several bone grafting materials were proposed for bone regeneration, such as autogenous, allogenic and xenogenic biomaterials, or a combination of them and, as the biological response of host tissue can be related to biomaterial origin, attention was focused on the interactions occurring between grafts and host tissue. 1,2 As already reported by Mangano et al, heterologous biomaterials were found to be as clinically efficient as autologous bone for their capacity of osteoconduction, even if little is known about their capability to be resorbed, and about the time they need to be fully replaced by newly formed bone tissue. 3 In fact, a biomaterial showing a too rapid resorption rate may result unsuitable for bone augmentation procedures, because it could be completely resorbed before osteogenic cells have colonized the defect; on the other hand, a biomaterial showing no resorption could cause problems to the regeneration of bone with a lower osteogenesis ability in respect to native autologous bone.…”
Section: Introductionmentioning
confidence: 75%
“…Several bone grafting materials were proposed for bone regeneration, such as autogenous, allogenic and xenogenic biomaterials, or a combination of them and, as the biological response of host tissue can be related to biomaterial origin, attention was focused on the interactions occurring between grafts and host tissue. 1,2 As already reported by Mangano et al, heterologous biomaterials were found to be as clinically efficient as autologous bone for their capacity of osteoconduction, even if little is known about their capability to be resorbed, and about the time they need to be fully replaced by newly formed bone tissue. 3 In fact, a biomaterial showing a too rapid resorption rate may result unsuitable for bone augmentation procedures, because it could be completely resorbed before osteogenic cells have colonized the defect; on the other hand, a biomaterial showing no resorption could cause problems to the regeneration of bone with a lower osteogenesis ability in respect to native autologous bone.…”
Section: Introductionmentioning
confidence: 75%
“…As cell adhesion plays a critical role in cell morphology and function (Falconi et al 2007, Tetè et al 2009) and different stimuli can influence fibroblast adhesion (Liu et al 2010), fibroblast expression of pro-collagen I, a molecule involved in adhesive processes, was analysed by immunohistochemical and western blot analyses. The data strongly support pro-collagen I expression reduction in HGF samples after 48- and 72-h HEMA treatment and show perinuclear localization of protein in control samples.…”
Section: Discussionmentioning
confidence: 99%
“…27 The high level of IL-1 and TNFa released in vitro at day 7 could resemble the inflammatory response that arises from the first interaction between an implant surface or, in general, a biomaterial with the host tissue. 28,29 However, IL-6 and PGE 2 are usually described as stimulators for osteoclast activity. 30 In particular, the latter could be responsible in vivo for the recruitment and for the osteoclastic cell activation, which is responsible of bone tissue resorption.…”
Section: Discussionmentioning
confidence: 99%